Differential Physiological, Transcriptomic, and Metabolomic Responses of Paspalum wettsteinii Under High-Temperature Stress - Zhao, Xin; Huang, Li-Juan; Sun, Xiao-Fu; Zhao, Li-Li; Wang, Pu-Chang (Frontiers in Plant Science, 2022)
Global warming has far-reaching effects on plant growth and development. As a warm-season forage grass, Paspalum wettsteinii is highly adaptable to high temperatures. However, the response mechanism of P. wettsteinii under high-temperature stress is still unclear. Therefore, we investigated the physiological indicators, transcriptome and metabolome of P. wettsteinii under different heat stress treatments. Plant height, the activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT), and the contents of soluble sugar, proline, chlorophyll a and chlorophyll b increased and then decreased, while the malondialdehyde (MDA) content decreased and then increased with increasing heat stress. Transcriptomic analysis revealed that genes related to energy and carbohydrate metabolism, heat shock proteins and transcription factors, secondary metabolite biosynthesis, and the antioxidant system significantly changed to varying degrees. Metabolomic analysis showed that only free fatty acids were downregulated, while amino acids and their derivatives, organic acids, flavonoids and sugars were both up- and downregulated under heat stress. These combined analyses revealed that growth was promoted at 25°C-40°C, while at 45°C, excess reactive oxygen species (ROS) damage reduced antioxidant and osmoregulatory effects and inactivated genes associated with the light and electron transport chains, as well as damaged the PS II system and inhibited photosynthesis. A small number of genes and metabolites were upregulated to maintain the basic growth of P. wettsteinii. The physiological and biochemical changes in response to high-temperature stress were revealed, and the important metabolites and key genes involved in the response to high temperature were identified, providing an important reference for the physiological and molecular regulation of high-temperature stress in plants.